Myosin B of plasmodium falciparum (PfMyoB): in silico prediction of its three-dimensional structure and its possible interaction with MTIP (2017)
The mobility and invasion strategy of Plasmodium falciparum is governed by a protein complex known as the glideosome, which contains an actin-myosin motor. It has been shown that myosin A of the parasite (PfMyoA) is the myosin of the glideosome, and the interaction of PfMyoA with myosin tail domain interacting protein (MTIP) determines its correct location and its ability to function in the complex. Because PfMyoA and myosin B of P. falciparum (PfMyoB) share high sequence identity, are both small proteins without a tail domain, belong to the class XIV myosins, and are expressed in late schizonts and merozoites, we suspect that these myosins may have similar or redundant functions. Therefore, this work examined the structural similarity between PfMyoA and PfMyoB and performed a molecular docking between PfMyoB and MTIP. Three-dimensional (3D) models obtained for PfMyoA and PfMyoB achieved high scores in the structural validation programs used, and their superimposition revealed high structural similarity, supporting the hypothesis of possible similar functions for these two proteins. The 3D interaction models obtained and energy values found suggested that interaction between PfMyoB and MTIP is possible. Given the apparent abundance of PfMyoA relative to PfMyoB in the parasite, we believe that the interaction between PfMyoB and MTIP would only be detectable in specific cellular environments because under normal circumstances, it would be masked by the interaction between PfMyoA and MTIP.